“We must be mentally strong”: exploring barriers to mental health in correctional services - Coulling, Ryan; Johnston, Matthew S.; Ricciardelli, Rosemary (Frontiers in Psychology, 2024)
The inherent nature of work in correctional services can have negative effects on correctional worker mental health and well-being. The current study, a replication, analyzes survey data collected from provincial and territorial correctional workers staffed in six regions across Canada (n = 192). Specifically, participants were asked at the end of an extensive mental health and well-being survey an open-ended question requesting any additional feedback or information.Four predominant themes were identified in the data: (1) stigma pertaining to a need to recognize mental health concerns within correctional services; (2) the idea that correctional services wear on the mind and body; (3) a need for better relationships with and support from correctional supervisors, upper management, and ministerial leadership; and (4) suggestions to improve correctional services to help the sector realize its full potential and maximize workplace health.We discuss the implications of these findings, with an emphasis on finding ways to promote positive organizational and cultural change in correctional services.